2014
DOI: 10.1111/nep.12202
|View full text |Cite
|
Sign up to set email alerts
|

Decreased mobility after starting dialysis is an independent risk factor for short‐term mortality after initiation of dialysis

Abstract: Not only impaired mobility at the start of dialysis but also a decline in mobility after starting dialysis is associated with short-term mortality after initiation of dialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…The prevalence of impaired mobility in patients reaching ESRD was 7%-34% among the included studies (32)(33)(34)(35)(36)(37)(38)(39). Nine studies addressed mobility, and all nine reported immobility to be significantly associated with a higher risk of mortality, independent of sex and calendar age (32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of impaired mobility in patients reaching ESRD was 7%-34% among the included studies (32)(33)(34)(35)(36)(37)(38)(39). Nine studies addressed mobility, and all nine reported immobility to be significantly associated with a higher risk of mortality, independent of sex and calendar age (32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
“…Nine studies addressed mobility, and all nine reported immobility to be significantly associated with a higher risk of mortality, independent of sex and calendar age (32)(33)(34)(35)(36)(37)(38)(39)(40). Mobility status was assessed in all studies by using data on whether the patient was dependent for transfers and walking without objectifying actual mobility (for instance, by measuring gait speed).…”
Section: Association Of Functional or Cognitive Impairment And Frailtmentioning
confidence: 99%
“…Depressive symptoms were present in 24%-55% of patients in the studies that applied a systematic assessment (20,23,27,35), whereas the prevalence of the International Statistical Classification of Diseases diagnosis depression ranged from 4% to 28% (23,29,39,41). Prevalence of cognitive impairment ranged from 6% to 13% in general (25,26,29,31,40) and was 41% in the very old (18). No studies assessed the relation between falls or social environment and poor outcome in the incident dialysis population.…”
Section: Assessment and Prevalence Of Geriatric Impairmentsmentioning
confidence: 99%
“…However, when focusing on the database studies, which included the vast majority of patients, depressive symptoms were associated with mortality in two studies (OR, 1.30; 95% CI, 1.00 to 1.60 [41] and OR, 1.08; 95% CI, 1.01 to 1.14 [35]), and in one study, depression was associated with noncardiovascular mortality (HR, 1.94; 95% CI, 1.10 to 3.42 [20]). In elderly patients, impaired mobility was associated with 1-year mortality in an univariate analysis of a single publication (OR, 4.22; 95% CI, 1.87 to 9.57) (18), and total dependence for transfers was independently associated with 3-and 6-month mortality (OR, 6.53; 95% CI, 5.38 to 7.92 and OR, 1.7; 95% CI, 1.4 to 2.0, respectively) (25,26). Dependence in ADLs was associated with mortality in two of three studies (OR, 1.41; 95% CI, 1.08 to 1.85) (31,42).…”
Section: Relation Of Geriatric Impairments and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation